Belt Road initiative(BRI):Global Strategy of Economic & Politic Made in China - Hoy Yam Jim (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
This article is a brief exploring of BRI (Belt Road Initiative) which is launched on 2013 in China and worked by double spearheads covered global economic and politic relationship of counterpart countries. By the record, BRI has 139 counterpart countries in the world. It shown quite succeed endeavor; since China achieve it in short time, relatively. Some highlight points of the exploring are the sense of initiative regarding to raise up historical memories of Silk Road and basic international trade theory of Comparative Advantage, which is innovated and applied on contemporary global economic and politic practices. At the eventually, this paper is concluded that BRI???s way is worth to be adopted as a model to build an advantage business strategy.